“I Saw It in a Dream”: Moroccan Women Ša‘bī Musicians in Brussels - Sechehaye, Hélène; Amezian, Laïla (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2022)
The Moroccan community is one of the largest national communities in Belgium. Several all-female bands are active at Moroccan weddings in Brussels, specialising in many genres, including ša‘bī (“popular”). This article focuses on the trajectories of these musicians, highlighting the obstacles they have faced as women in the Moroccan–Brussels community, and as migrant women in Brussels society. This article also examines different aspects of what it means to be a woman musician in the field of ša‘bī music: calling, education, musical skills, and musical activity, exploring the tension between their role as “ordinary” musicians and the crucial role they play in the most important events of one’s life.